Overview of Speaker Recognition - Rosenberg, Aaron; Bimbot, Frederic; Parthasarathy, Sarangarajan (Springer Handbook of Speech Processing, 2008)
An introduction to automatic speaker recognition is presented in this chapter. The identifying characteristics of a personʼs voice that make it possible to automatically identify a speaker are discussed. Subtasks such as speaker identification, verification, and detection are described. An overview of the techniques used to build speaker models as well as issues related to system performance are presented. Finally, a few selected applications of speaker recognition are introduced to demonstrate the wide range of applications of speaker recognition technologies. Details of text-dependent and text-independent speaker recognition and their applications are covered in the following two chapters.